Prevalence of skin diseases among hostellers attending the tertiary care hospital - Abirami P,; Narmadha S, (Asian Journal of Medical Sciences, 2024)
Background: Skin diseases are more common but are mostly non-fatal and chronic. Dermatological conditions account for a significant proportion of the global burden of diseases. Aims and Objectives: The study aimed to determine the prevalence of skin diseases among hostellers, determine the causative factors, and describe the prevention. Materials and Methods: This cross-sectional study was conducted for 2 months in the outpatient Department of Dermatology, Government Medical College, Pudukottai, on 507 hostellers. The study subjects were examined and diagnosed by the dermatologist. Questions such as exposure to sunlight, usage of sunscreen, frequency of head baths, and junk food consumption were asked and recorded in a case study form by the principal investigator. Results: Pityriasis capitis was the most prevalent skin disease among 507 participants, followed by acne vulgaris (54.83%) and pediculosis capitis (25.64%). Pityriasis capitis is more common in men (56.17%), with higher chances in those with head baths (<3 times/week) and exposure to sunlight (28.08%). Acne vulgaris affects both males and females equally; face washing <3 times daily is associated with oil and sebum retention, while lack of sunscreen and junk food intake are linked. Periorbital melanosis is more prevalent in females (54.62%) and is linked to stress (66.39%). Sleep duration is also a factor, with 69.23% of girls having a history of cosmetic usage. Conclusion: Pityriasis capitis, acne vulgaris, pediculosis capitis, dermatophytosis, and periorbital melanosis are common skin diseases caused by sharing, sleep deprivation, stress, and poor hygiene. Proper hygiene, sleep patterns, and self-care can reduce skin disease incidence.